Political cleavages, party voter linkages and the impact of voters’ socio-economic status on vote-choice in Iceland, 1983-2016/17 - Önnudóttir, Eva H.; Harðarson, Ólafur Þ. (Stjórnsýslustofnun, 2018)
In the research presented in this paper, we analyse whether the structure of the political cleavage system in Iceland has changed since 1983, as well as whether the impacts of party-voter linkages and the social structure of the vote have changed between 1983 and 2016/2017. Based on official data and the Icelandic National Election Study (ICENES), we find that the rural-urban cleavage and left-right cleavage, which are reflected in party polarisation on the left-right spectrum, are as important today as previously. Our main results regarding the impacts of party-voter linkages and the social-structure of the vote is that the core bonds of party identification, left-right distances and the social structure of the vote have weakened over time, whereas the impact of party sympathy has become stronger. This, we argue, reflects that while there has been a gradual change in the impact of party-voter linkages and the social structure of the vote, opening up a space for new parties to succeed, the political cleavage system has remained intact. The major change has thus occurred in the bond between voters and parties and not in the structure of party competition in Iceland.